Direct Consequences of Cranioplasty to the Brain: Intracranial Pressure Study. Issue 8 (9th November 2021) - Tsianaka, Eleni; Singh, Ajit; Drosos, Evangelos; Fountas, Kostas
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Intracranial pressure (ICP) is a crucial factor that we need to take into account in all major pathophysiological changes of the brain after decompressive craniectomy (DC) and cranioplasty (CP). The purpose of our study was to check ICP values before and after cranioplasty and its relation to various parameters (imaging, demographics, time of cranioplasty, and type of graft) as well as its possible relation to postsurgical complications. The authors performed a prospective study in which they selected as participants adults who had undergone unilateral frontotemporoparietal DC and were planned to have cranioplasty. Intracranial pressure was measured with optical fiber sensor in the epidural space and did not affect cranioplasty in any way. Twenty-five patients met the criteria. The mean vcICP (value change of ICP) was 1.2 mm Hg, the mean ΔICP (absolute value change of the ICP) was 2.24 mm Hg and in the majority of cases there was an increase in ICP. The authors found 3 statistically significant correlations: between gender and ΔICP, Δtime (time between DC and CP) and vcICP, and pre-ICP and ±ICP (quantitative change of the ICP). Μale patients tend to develop larger changes of ICP values during CP. As the time between the 2 procedures (DC and CP) gets longer, the vcICP is decreased. However, after certain time it shows a tendency to remain around zero. Lower pre-ICP values (close to or below zero) are more possible to increase after bone flap placement. It seems that the brain tends to restore its pre-DC conditions after CP by taking near-to-normal ICP values.